In Defence of Stakeholder Pragmatism - Jensen, Tommy (Journal of business ethics, 2013)
This article seeks to defend and develop a stakeholder pragmatism advanced in some of the work by Edward Freeman and colleagues. By positioning stakeholder pragmatism more in line with the democratic and ethical base in American pragmatism (as developed by William James, John Dewey and Richard Rorty), the article sets forth a fallibilistic stakeholder pragmatism that seeks to be more useful to companies by expanding the ways in which value is and can be created in a contingent world. A dialogue between a defence company and peace and arbitration society is used to illustrate the main plot of this article.